Comparison of the Essential Oils of Ferula orientalis L., Ferulago sandrasica Peşmen and Quézel, and Hippomarathrum microcarpum Petrov and Their Antimicrobial Activity - KARAKAYA, Songül (Turk J Pharm Sci, 2019)
OBJECTIVES: To determine the chemical composition and antimicrobial activity of the essential oils of the aerial parts of Ferula orientalis L., roots of Ferulago sandrasica Peşmen and Quézel, and aerial parts of Hippomarathrum microcarpum Petrov. MATERIALS AND METHODS: Essential oils were analyzed by gas chromatography and gas chromatography/mass spectrometry. The antimicrobial activity of the essential oils was determined by bioautography assay. RESULTS: α-Pinene (75.9%) and β-pinene (3.4%) were the major components of the aerial parts of F. orientalis; with limonene (28.9%), α-pinene (15.6%), and terpinolene (13.9%) for F. sandrasica; and β-caryophyllene (31.4%) and caryophyllene oxide (23.1%) for the aerial parts of H. microcarpum. Essential oils from the aerial parts of F. orientalis, the roots of F. sandrasica, and the aerial parts of H. microcarpum were active against Staphylococcus aureus and Candida albicans strains. However, essential oils were not active against Pseudomonas aeruginosa or Escherichia coli. CONCLUSION: The antimicrobial activities against S. aureus and C. albicans of these species may be attributed to the presence of the main components in the essential oils.